Tandem aldehyde–alkyne–amine coupling/cycloisomerization: A new synthesis of coumarins - Reddy, Maddi Sridhar (Beilstein-Institut, 2013)
Cu-catalyzed A(3) coupling of ethoxyacetylene, pyrrolidine and salicylaldehydes led to a concomitant cycloisomerization followed by hydrolysis of the resultant vinyl ether to afford coumarins in a cascade process. The reaction proceeded through exclusive 6-endo-dig cyclization and is compatible with halo and keto groups giving coumarins in good to moderate yields.